Kepemimpinan Kerajaan Allah Berdasarkan Ucapan Bahagia Ajaran Yesus Kristus Matius 5:3-12 - Kuncoro Condro (SANCTUM DOMINE: JURNAL TEOLOGI, 2019)
Christian leadership is leadership based on the principles of Christian belief that are built on biblical truth. The Community of God's Kingdom built by Jesus Christ is a different group from other groups in the world. Therefore the right leadership applied in leadership here is leadership that is not based on violence and authoritarianism but rather humble, afraid of sin, gentle, like truth, full of mercy, pure heart, peaceable, ready to suffer.